Bergenin ameliorates airway inflammation and remodeling in asthma by activating SIRT1 in macrophages to regulate the NF-κB pathway - Huang, Dan; Sun, Chaoqun; Chen, Min; Bai, Shuyou; Zhao, Xuanna; Wang, Weiming; Geng, Kang; Huang, Wenbo; Zhao, Tingting; Wu, Bin; Zhang, Guilin; Wu, Dong; et al. (Frontiers in Pharmacology, 2022)
Airway inflammation and remodeling are critical pathological changes in asthma, and macrophage activation plays a vital role in this process. Sirtuin 1 (SIRT1) reduces airway inflammation by affecting macrophages in asthma. This study aimed to investigate the potential benefit and underlying mechanism of the SIRT1 agonist bergenin as a treatment for asthma. We performed in vivo and in vitro experiments by establishing a Sirt1fl/fl-LysMcre mouse asthma model and using the alveolar macrophage-like cell line MH-S, respectively. Our results show that Sirt1fl/fl-LysMcre asthmatic mice exhibited more severe airway inflammation and airway remodeling than wild-type mice. As an activator of SIRT1, bergenin attenuated asthmatic airway pathology and reduced production of interleukins 1β and 6 (IL-1β and IL-6), and matrix metalloproteinase 9 (MMP-9) in wild-type asthmatic mice. However, the therapeutic effects of bergenin were significantly attenuated in Sirt1fl/fl-LysMcre asthmatic mice or following coadministration with the SIRT1 inhibitor EX-527. Further experiments showed that activation of SIRT1 by bergenin deacetylates nuclear factor κB and hinders its nuclear translocation, thereby affecting IL-1β, IL-6, and MMP-9 production by regulating transcriptional activity. Our study suggests that bergenin can improve asthma-induced airway inflammation and remodeling by activating SIRT1 in macrophages.